DOCTORS' ONLINE EDUCATION: LIMITATIONS OF CULTURAL CAPITAL CONVERSION - Larisa E. Petrova (Moscow Polytechnic University, 2016)
The article views a group of three sources of medical online education for professionals: MOOC - massive open online courses, educational portals with video, and professional social networks. The author dwells on a problem of a conflict between the demand for medical online education and the possibility of a formal conversion of such resources. Due to certain legal limitations Russian medical students and practitioners can use online resources only as informal education or selfHeducation.